The Grammatical Deviations in The Arabic Debate Competition in Indonesia - Rika Astari; Alvinda Yunaz; Muhammad Irfan Faturrahman (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2022)
This study aimed to describe the form of Arabic grammatical errors that occur in the Arabic debate competition in Indonesia both off-line and on-line, the factors, the impact, and solutions for grammatical errors. The material object of this research was the video of the Arabic debate competition in Indonesia. This study used a qualitative descriptive approach to grammatical errors in the video of the Arabic debate competition in Indonesia. The results showed that 29 grammatical errors were found in syntax errors and 18 morphological errors. From the 47 errors found, the factors were inter-language errors or interference and intra-language errors. These factors have an impact on changing the meaning of a sentence and also have an impact on misunderstanding communication between speakers. The solutions offered to improve and reduce the error are the need for good preparation in syntactic and morphological aspects for debaters before competing, conducting intensive training, and increasing seriousness in exploring and understanding Arabic debate.